Applicability of the 210Pb dating method to quartz-sandstone stalactites - Figols, André P. [UNESP]; Bonotto, Daniel M. [UNESP] (Springer Nature, 2022)
This paper describes the first application of the 210Pb dating method to quartz-sandstone stalactites, which until now had only been used to determine the growth rates of recent carbonate speleothems. Five stalactites were sampled from two quartz-sandstone caves located in Serra de Itaqueri, southeastern Brazil, and they all exhibited a quantifiable measure of the 210Pb activity concentration in their sectional layers. Two samples showed a desirable exponential decrease of the excess 210Pb activity along with the vertical distance, yielding growth rates of 0.39±0.08 mm/yr and 0.18±0.01 mm/yr, respectively, for stalactites 25-mm long (Paredão Cave) and 17-mm long (Fazendão cave).
Keywords: 210Pb dating method; Growth rates; Quartz-sandstone stalactites; Serra de Itaqueri caves